2012
DOI: 10.1073/pnas.1205726109
|View full text |Cite
|
Sign up to set email alerts
|

Casparian strip diffusion barrier in Arabidopsis is made of a lignin polymer without suberin

Abstract: Casparian strips are ring-like cell-wall modifications in the root endodermis of vascular plants. Their presence generates a paracellular barrier, analogous to animal tight junctions, that is thought to be crucial for selective nutrient uptake, exclusion of pathogens, and many other processes. Despite their importance, the chemical nature of Casparian strips has remained a matter of debate, confounding further molecular analysis. Suberin, lignin, lignin-like polymers, or both, have been claimed to make up Casp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
460
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 439 publications
(485 citation statements)
references
References 25 publications
21
460
3
1
Order By: Relevance
“…S2A and S3A). Propidium iodide (PI) is a fluorescent dye used as an apoplastic tracer whose movement into the inner cell layer of the stele is blocked by Casparian strips (2). Staining with PI revealed that esb1-1 shows delayed barrier development ( absence of ESB1, it is possible that polymerization of monolignols, usually directed by localized NADPH oxidases and peroxidases (6), does not proceed normally, as indicated by the islands of lignin observed in esb1-1.…”
Section: Significancementioning
confidence: 99%
“…S2A and S3A). Propidium iodide (PI) is a fluorescent dye used as an apoplastic tracer whose movement into the inner cell layer of the stele is blocked by Casparian strips (2). Staining with PI revealed that esb1-1 shows delayed barrier development ( absence of ESB1, it is possible that polymerization of monolignols, usually directed by localized NADPH oxidases and peroxidases (6), does not proceed normally, as indicated by the islands of lignin observed in esb1-1.…”
Section: Significancementioning
confidence: 99%
“…The endodermis protects the root vasculature from the entry of harmful toxins and pathogens by means of a cell-wall modification called the Casparian strip (1). This lignin-composed extracellular barrier prevents the passive flow of water and solutes into and out of the vasculature (2). To enter the vasculature, ions must pass through the endodermis, which selectively filters nutrients.…”
mentioning
confidence: 99%
“…18,19 Although exposing the rice under salinity stress leads to the deposition of suberin that further provides strength to the apoplastic barriers and such barriers block Na C transport to shoots. 16 The salinity tolerant variety (Pokkali) revealed more extensive hydrophobic barriers in its roots as compared to the salinity susceptible variety (IR20). 17,20 The PDH45 overexpression enhances salinity tolerance without compromising yield as compared to WT (IR64).…”
Section: Discussionmentioning
confidence: 99%
“…16 Further, bypass flow closely paralleled the extent of suberin deposition over the course of exposure to salinity stress and is negatively correlated with suberin deposits. 17 CoroNa Green AM binds with sodium (Na C ) and is specific Na C indicator that shows increase in fluorescence intensity indicates increasing Na C accumulation.…”
mentioning
confidence: 91%